Analysis of Electronic Modules in Enhancing Mathematics Learning Motivation in Elementary Schools - Utami, Sulistya; Firmansah, Deri; Yanti, Yuli (Institut Agama Islam Negeri Palopo, 2025)
The purpose of this study was to analyze the use of electronic modules in improving learning motivation in mathematics subjects in elementary schools. The method used is qualitative with a bibliometric analysis approach. Documents collected from the Publish or Perish (PoP) application using the Google Scholar database are then combined into one file in RIS format and entered into the VOSviewer application. The initial number of articles retrieved was 1000 and then narrowed down to 100 articles for analysis. Data analysis is the search stage, filtering stage, and bibliometric analysis stage. The results of the study showed that the year of publication that published the most articles and journals was 2023 with a total of 59 publications, then when viewed from the publishing institution, Ganesha University of Education has the highest number of documents, namely 6 documents and 106 citations. Meanwhile, when viewed from the publisher who published, the Scientific Journal of Education and Learning has the most document publications along with the number of citations. When viewed from the author, Yunita Lastri received 87 citations, making it the highest among other publications. When viewed from the keywords,